Skeletal muscle mass metrics as factors in the prognosis of heart failure patients. (11th May 2022) - Uchida, S; Kamiya, K; Hamazaki, N; Nozaki, K; Ichikawa, T; Yamashita, M; Noda, T; Maekawa, E; Yamaoka-Tojo, M; Matsunaga, A; Ako, J
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): JSPS KAKENHI Grant Background: Sarcopenia is a chronic condition that is characterized by the loss of skeletal muscle mass with declining muscle strength and/or performance that occurs gradually with aging. It has been reported that sarcopenia is highly prevalent in patients with heart failure (HF) and is a poor prognostic factor. Therefore, it is important to accurately assess skeletal muscle mass in patients with HF. However, there are no reports that have simultaneously examined different skeletal muscle mass metrics as factors in the prognosis of HF patients. Purpose: The purpose of this study is to examine if the different skeletal muscle mass metrics are associated with the prognosis of HF patients. Methods: We examined a total of 869 patients with HF, aged ≥20 years (73 [63, 80] years; 537 males), who were admitted to our hospital and participated in an inpatient cardiac rehabilitation program. We used skeletal muscle mass index (SMI) as measured by bioelectrical impedance analysis (BIA), mid-upper arm circumference (MUAC), arm muscle circumference (AMC), and calf circumference (CC) as metrics of skeletal muscle mass. The primary outcome was all-cause deaths, and secondary outcome was HF readmission. To investigate the association between each skeletal muscle mass metric and prognosis, patients were divided into three groups according to the tertiles of SMI, MUAC, AMC, and CC. In addition, cumulative event rates of survival curves, Gray test, and Fine & Gray test were performed to evaluate the prognostic predictive capability. Results: Over a median follow-up period of 0.9 years (interquartile 0.4–1.9) years, a total of 80 deaths and 195 HF readmissions occurred in the patients. Cumulative event rates of survival curves and Gray test showed that there was a significant decrease in all-cause mortality and HF readmission in the high MUAC group and high AMC group compared to their respective low groups (P < 0.05). Fine & Gray test after multivariate adjustment showed significantly better prognosis in the high MUAC group and high AMC group compared to their respective low groups (All-cause mortality: high MUAC group, subdistribution hazard ratio [sHR] = 0.42, 95% confidence interval [CI] = 0.20-0.88, P < 0.05; high AMC group, sHR = 0.34, 95%CI = 0.16-0.72 P < 0.05, HF readmission: high MUAC group, sHR = 0.69, 95%CI = 0.47-1.00, P < 0.05; high AMC group, sHR = 0.63, 95%CI = 0.43-0.93, P < 0.05). Conclusion: Patients with HF who maintained high MUAC and high AMC had a good prognosis. CC and SMI were not associated with the prognosis of HF patients. This suggests the importance of evaluating MUAC and AMC in HF patients.